PEMBIASAAN MEMBENTUK KARAKTEK PESERTA DIDIK DI MADRASAH ATH-THOHIRIYAH - Bella Afrianti; Husnul Awalia; Muhammad Iskandar; Miya Minarti; Lia Widyawati (TA'LIM : Jurnal Studi Pendidikan Islam, 2021)
The problem of this research is to reveal the problems faced by the character of students at the Musi Rawas Madrasah ATH-THOHIRIYAH Muara Bulian, Batanghari Jambi Regency. Although the purpose of this study is to understand the habituation of the nature of the students of Madrasah ATH-THOHIRIYAH, this research method is descriptive qualitative. So that the results of this study will be obtained, namely character building involves the application of the first, the value of worship such as praying in congregation, praying sunnah, reading the Qur'an, and praying. Second, it violates individual personality, such as honesty, manners, manners, discipline. The three supporting factors resulted from the commitment of the teacher and the willingness of students to apply the exemplary method. These inhibiting factors come from the environment and from individuals who are unable to control their desire to live freely.